Pemberdayaan ibu-ibu Desa Manukan Bojonegoro dalam mengembangkan Batik Jonegoroan sebagai rintisan industri kreatif - Ngatini Ngatini; Maulin Masyito Putri; Muhammad Faisal Ibrahim; Taufiqotul Bariyah; Yunita Siti Mardhiyyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Manukan is a village in Bojonegoro Regency which is located in Gayam, Bojonegoro, East Java. The lack of family income from farmer profession requires the community to be more creative in increasing family income. Though Bojonegoro has the potential of Jonegoroan batik, which is attractive and much in demand, not many Bojonegoro people have batik knowledge and skills. Therefore, it is necessary to empower women in developing the Jonegoroan Batik creative industry. It’s carried out through four stages: socialization of Batik Jonegoroan, training on how to make batik, training on developing the creative industries of batik and batik marketing. In this training, participants are trained to understand and practice the process of making batik with four technical coloring and differences between printed batik and written batik. The coloring techniques studied included colekan, semok, kelengan and laseman. Jonegoroan batik products are exhibited and sold online in marketplaces and social media, while offline in batik bazaars and exhibitions. This knowledge and skills can be used as provisions to open up business opportunities for batik craftsmen to increase family income.